Growth factors and management technique in relation to the developmental rhythm yield formation pattern of a seeding year lucerne stand - Pulli, Seppo (Agricultural and Food Science, 1980)
The investigation of seeding year Lucerne stand development and yield formation pattern was carried out at the University of Helsinki in Viikki in 1973—74. The management techniques studied were the number of cuttings and the density of stand establishment. The variety used was Danish Isis-Daenfeldt. The maximum DM yield was obtained from a seeding rate of 20 kg/ha. The maximum DM yield produced under the favourable growing conditions in 1973 was 5. 7 tons/ha and under the less favourable conditions in 1974 3.3 tons/ha. No more than two cuts in the year of seeding are recommended. The radiation used by lucerne was 0.3—0.5 %of the total radiation reaching the surface. A 10% decrease in radiation in 1974 resulted in a 50 % decrease in photosynthetic activity mainly due to differences in temperature and overabundant precipitation. The optimum LAI was obtained from seedingrates ≥5 kg/ha. From seeding to emergence a temperature sum of 120 °C is needed and from seeding to flowering a sum of 800°C. From cutting to the next flowering a sum of 600— 700°C is needed. Three cuts provided forage 6.3 % units more digestible than two cuts. Root carbohydrate levels suggest that the last cut should not be made later than mid-August.